2021
DOI: 10.31080/aswh.2021.03.0264
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Vitamin D and Autoimmune Condition and Thyroid Function with Newly Onset Grave’s Disease

Abstract: Vitamin due to the presence of the receptor (VDR), which is found in almost all nuclear cells is an important regulator in the pathogenesis of many diseases. The question of the causal relationship between vitamin D deficiency and Graves 'disease and the importance of this vitamin for thyroid function in the treatment of Graves' disease deserves special attention. The aim of the study was to investigate the level of 25-(OH) D in the body in Graves' disease and its relationship with thyroid function. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
2
0
0
6
Order By: Relevance
“…TSH levels also increased and FT4 decreased, but the differences weren't statistically significant (p=0.328 & 0.267 respectively). These results are similar to Kravchenko et al (24) who found that taking vitamin D supplement seems to improve thyroid function (increase in serum TSH values and a decline in thyroid volume) in Graves' patients. Also, Sheriba and his colleagues (29) studied 60 individuals with GD; 40 received a 30 mg of methimazole and 200000IU of vitamin D per month for 3 months, while the remaining 20 received methimazole alone and reported that Vitamin D administration has favorable effects on the degree of exophthalmos as well as on thyroid volume.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…TSH levels also increased and FT4 decreased, but the differences weren't statistically significant (p=0.328 & 0.267 respectively). These results are similar to Kravchenko et al (24) who found that taking vitamin D supplement seems to improve thyroid function (increase in serum TSH values and a decline in thyroid volume) in Graves' patients. Also, Sheriba and his colleagues (29) studied 60 individuals with GD; 40 received a 30 mg of methimazole and 200000IU of vitamin D per month for 3 months, while the remaining 20 received methimazole alone and reported that Vitamin D administration has favorable effects on the degree of exophthalmos as well as on thyroid volume.…”
Section: Discussionsupporting
confidence: 90%
“…We found that Graves' cases with VDI had a significant decrease in TRAB, anti-TPO, and anti-Tg titers after taking VD supplements for six months (p<0.001, 0.039, and 0.007, respectively). These results are in accordance with Kravchenko and his colleagues (24) who reported a significant decrease in TRAB titers in Graves' cases after vitamin D intake and came to the conclusion that, autoimmune thyroid illnesses can be prevented, or their clinical symptoms can be diminished by using vitamin D in optimal dose. There are a limited number of research on the actions of VD supplementation in GD, but those that are available seem to indicate that it has a positive impact.…”
Section: Discussionsupporting
confidence: 90%
“…У 51,7% обстежених спостерігали знижений рівень се лену -<60 мкг/л. При ХГ рівень селену в си роватці крові був майже вдвічі нижчим, ніж у контрольній групі та становив 29,35 мкг/л (р<0,001) [61]. У межах нормальних значень було тільки 26,6% проб.…”
Section: забезпечення селеном та стан щз при хгunclassified
“…Суттєві позитивні зміни реєструвалися в рівні АТрТТГ в крові, причому з подовженням лі кування до 6 місяців ця позитивна тенденція зберігалася (р<0,005). Порівнюючи з показни ком у контрольній групі титр АТрТТГ все ж залишався підвищеним [61].…”
Section: забезпечення селеном та стан щз при хгunclassified
“…Через 3 місяці лікування рівень антитіл до рецептора тиреотропого гормону в сироватці крові при лікуванні додатково вітаміном Д був вдвічі нижчим, ніж при лікуванні тільки тирозолом. Через 6 місяців порівняно з лікуванням тирозолом ефект лікування був ще у 2 рази кращим [36].…”
Section: дослідження співробітників відділу за останні 5 роківunclassified